Aminadab - Aram/Adam - Admin - Arni in Luke 4,33 - Brandão, Jacyntho Lins (Filología neotestamentaria, 2011)
This paper examines the issue of the variant readings of the names of Aminadab and Aram in the genealogy of Jesus, presenting the hypothesis that the reading Adam-Admin-Arni may illuminate the pretextual stages of Luke, when we consider the manner in which ancient writers worked. Proceeding from the OT, in the hypomnemata of Luke or his source the list from Adam to David was probably written down in columns, with the names one under the other, following the hereditary line, as is the usual form of genealogies. In this list, Aminadam and Arni proceed from Aminadab and Aram, a mistake that is paleographically justifiable, taking cursive script into account. Being a longer name, Aminadam would have been divided into two lines. As Luke’s genealogy is in ascending order, Aminadam would have generated two names, Adam and Amim. Admin proceeds from the latter, through the dittography of triangular letters in an uncial script.